Collaborative Governance in border management policies to support national defense (a case study on the land border of West Kalimantan Province) 093-2103 - et. al., Eko Bambang Wibowo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indonesia is an archipelagic state with a very large area and borders with 10 countries, both inland and sea areas. One of Indonesia's land border areas is located in West Kalimantan Province which is directly adjacent to the state of Sarawak, Malaysia. The border is a very strategic area with problem complexity. Therefore, it requires proper and comprehensive management efforts from the government. This study aims to analyze one of the dimensions of collaborative governance, namely the collaborative process in the management of territorial boundaries in West Kalimantan Province to support national defense. This article is compiled based on the results of a qualitative descriptive study. The data in this study were obtained using interview techniques, direct observation, and literature study. The data is then analyzed using qualitative data analysis techniques which include the following activities: data collection, data reduction, data presentation, and verification. Based on data analysis and discussion, this border area is managed by several stakeholders, both government and non-government, so that proper collaboration is needed in the formulation of border area management policies to be effective, efficient, and right on target. The collaborative process in collaborative governance includes five elements of the collaborative process, namely: face-to-face dialogue, building trust, commitment to the process, mutual understanding, and intermediate results. The results of this study are expected to become one of the fundamental foundations for the Indonesian government, particularly in the formulation and implementation of policies related to land border management to defend the sovereign territory of Indonesia..